Damage sensing mediated by serine proteases Hayan and Persephone for Toll pathway activation in apoptosis-deficient flies. - Shotaro Nakano; Soshiro Kashio; Kei Nishimura; Asuka Takeishi; Hina Kosakamoto; Fumiaki Obata; Erina Kuranaga; Takahiro Chihara; Yoshio Yamauchi; Toshiaki Isobe; Masayuki Miura (PLoS Genetics, 2023)
The mechanisms by which the innate immune system senses damage have been extensively explored in multicellular organisms. In Drosophila, various types of tissue damage, including epidermal injury, tumor formation, cell competition, and apoptosis deficiency, induce sterile activation of the Toll pathway, a process that requires the use of extracellular serine protease (SP) cascades. Upon infection, the SP Spätzle (Spz)-processing enzyme (SPE) cleaves and activates the Toll ligand Spz downstream of two paralogous SPs, Hayan and Persephone (Psh). However, upon tissue damage, it is not fully understood which SPs establish Spz activation cascades nor what damage-associated molecules can activate SPs. In this study, using newly generated uncleavable spz mutant flies, we revealed that Spz cleavage is required for the sterile activation of the Toll pathway, which is induced by apoptosis-deficient damage of wing epidermal cells in adult Drosophila. Proteomic analysis of hemolymph, followed by experiments with Drosophila Schneider 2 (S2) cells, revealed that among hemolymph SPs, both SPE and Melanization Protease 1 (MP1) have high capacities to cleave Spz. Additionally, in S2 cells, MP1 acts downstream of Hayan and Psh in a similar manner to SPE. Using genetic analysis, we found that the upstream SPs Hayan and Psh contributes to the sterile activation of the Toll pathway. While SPE/MP1 double mutants show more impairment of Toll activation upon infection than SPE single mutants, Toll activation is not eliminated in these apoptosis-deficient flies. This suggests that Hayan and Psh sense necrotic damage, inducing Spz cleavage by SPs other than SPE and MP1. Furthermore, hydrogen peroxide, a representative damage-associated molecule, activates the Psh-Spz cascade in S2 cells overexpressing Psh. Considering that reactive oxygen species (ROS) were detected in apoptosis-deficient wings, our findings highlight the importance of ROS as signaling molecules that induce the activation of SPs such as Psh in response to damage.